KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA KELAS XI SMA NEGERI 1 MARGAASIH KABUPATEN BANDUNG - Nursari Endah; Euis Eti Rohaeti; Ecep Supriatna (IKIP Siliwangi, 2021)
This study aims to determine the profile of students' interpersonal communication skills. As for the aspects taken in interpersonal communication are the aspects of openness, empathy, equality and a positive attitude. This research was conducted on the subject of students of class XI as many as 156 students. In this study using quantitative descriptive methods with techniques data collection through interpersonal communication questionnaires. The scale used is linkert scale which contains statements of indicators of several aspects of interpersonal communication. The results obtained show that students with low interpersonal communication categories are 12%, moderate interpersonal communication categories are 66% and high interpersonal categories are 22%, thus it can be concluded that students who have low interpersonal communication need group guidance services to develop their competence. can live the life to comeKeywords: : Interpersonal communication, group guidance services